(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
Gender, discourse, and identity constitute central analytical categories across the social sciences and humanities, reflecting sustained scholarly attention to the ways identities are constructed, negotiated, and transformed through language. Although gender has been widely examined from linguistic, sociological, and psychological perspectives, these approaches are often pursued in relative isolation, limiting their explanatory potential. This article addresses this gap by developing a multidisciplinary theoretical framework that conceptualizes gender identity as a discursively constructed and socially mediated phenomenon. Drawing on critical discourse analysis, social identity theory, feminist scholarship, and post-structuralist thought, the study reconceptualizes gender not as a fixed or inherent attribute, but as a dynamic process shaped through discourse, power relations, and social interaction. The article critically engages with key theoretical contributions by Michel Foucault, Judith Butler, Norman Fairclough, Henri Tajfel, and Guli Ergasheva, highlighting the intersections between language, ideology, and identity formation. By synthesizing insights from linguistics, sociology, and psychology, the proposed framework demonstrates how gender identities are produced, stabilized, and contested across institutional, media, and everyday discourses. The article contributes to contemporary debates in gender and discourse studies by offering an integrative model capable of capturing the complexity of identity construction across disciplinary boundaries, with important implications for future theoretical and empirical research in applied linguistics and the social sciences.